Sistem Informasi Pengelolaan Zakat Dan Infaq Menggunakan Metode RAD - Aida Fitriyani; Rafika Sari; Sulhan Faiz (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2021)
Yayasan Masjid Miftahul Jannah Cibitung is one of the organizations engaged in religious worship, which has developed and always wants to keep up with the developing information technology. So far, the area of mosque administration still feels difficult to do because it uses a manual format. This has attracted the author to research and develop a web-based mosque information system. Therefore, the researcher proposes a web-based information system that will replace data collection and distribution of zakat and infaq management financial funds at the Baitul Maal Masjid Miftahul Jannah by using a web-based information system. The purpose of this research is to design and build an information system needed by Baitul Maal officers by using the Rapid Application Development method as a development method. The supporting software used in designing this youth information system is PHP and MySQL database. The final result of this research is that the existence of this information system can assist Baitul Maal officers in processing data recording and funding transactions of incoming and outgoing funds. And can reduce the risk of loss and damage to activity data because this application data that has been inputted will be stored in the database server.